Sodium‐glucose co‐transporter 2 inhibitors in addition to insulin therapy for management of type 2 diabetes mellitus: A meta‐analysis of randomized controlled trials. Issue 1 (29th September 2016) - Tang, Huilin; Cui, Wei; Li, Dandan; Wang, Tiansheng; Zhang, Jingjing; Zhai, Suodi; Song, Yiqing
Abstract : Given inconsistent trial results of sodium‐glucose cotransporter 2 (SGLT2) inhibitors in addition to insulin therapy for treating type 2 diabetes mellitus (T2DM), a meta‐analysis was performed to evaluate the efficacy and safety of this combination for T2DM by searching available randomized trials from PubMed, Embase, CENTRAL andClinicalTrials.gov . Our meta‐analysis included seven eligible placebo‐controlled trials involving 4235 patients. Compared with placebo, SGLT2 inhibitor treatment was significantly associated with a mean reduction in HbA1c of −0.56%, fasting plasma glucose of −0.95 mmol/L, body weight of −2.63 kg and insulin dose of −8.79 IU, but an increased risk of drug‐related adverse events by 36%, urinary tract infections by 29% and genital infections by 357%. No significant increase was observed in risk of overall adverse events [risk ratio (RR), 1.00], serious adverse events (RR, 0.90), adverse events leading to discontinuation (RR, 1.16), hypoglycaemia events (RR, 1.07) and severe hypoglycaemia events (RR, 1.24). No diabetic ketoacidosis events were reported. Further studies are needed to establish optimal combination type and dose.